2017
DOI: 10.1155/2017/7073401
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Volatile Anesthetic Choice on Postoperative Outcomes of Cardiac Surgery: A Meta-Analysis

Abstract: Objectives To evaluate the impact of volatile anesthetic choice on clinically relevant outcomes of patients undergoing cardiac surgery. Methods Major databases were systematically searched for randomized controlled trials (RCTs) comparing volatile anesthetics (isoflurane versus sevoflurane) in cardiac surgery. Study-level characteristics, intraoperative events, and postoperative outcomes were extracted from the articles. Results Sixteen RCTs involving 961 patients were included in this meta-analysis. There wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
0
3
0
4
Order By: Relevance
“…The choice of volatile anesthetic does not appear to affect clinical results. Isoflurane and sevoflurane were found to have no difference in patient outcomes [39].…”
Section: Anesthetic Managementmentioning
confidence: 92%
“…The choice of volatile anesthetic does not appear to affect clinical results. Isoflurane and sevoflurane were found to have no difference in patient outcomes [39].…”
Section: Anesthetic Managementmentioning
confidence: 92%
“…Se ha visto que con la anestesia inhalada los casos presentan niveles menores de troponina en comparación con aquéllos en los que se usó anestesia intravenosa. 31 La anestesia inhalada, según varios estudios, podría ser considerada como la ideal en la Unidad de Cuidados Intensivos. 32 A pesar de las teorías en las que el uso de la anestesia inhalada es beneficioso para pacientes de cirugía cardiaca, no existe aún suficiente evidencia que lo sustente.…”
Section: ¿Cuáles Son Los Beneficios Del Uso De Anestesia Inhalada En ...unclassified
“…Animal studies reported reduced neuronal death in the hippocampus of rats when a dose of 1–1.5 minimum alveolar concentration (MAC) of a volatile agent was given 15–30 min before circulatory arrest and at least 0.5 MAC of sevoflurane was given prior to commencement of CPB [ 49 ]. A meta-analysis comparing isoflurane and sevoflurane’s neuroprotective capabilities concluded that the choice of a volatile anaesthetic agent does not affect postoperative outcomes in cardiac surgery [ 53 ].…”
Section: Neuroprotection Interventionsmentioning
confidence: 99%